Antibacterial porous ceramic microbeads and preparation method thereof
By combining sol-gel method and microsphere foaming agent, antibacterial porous ceramic microbeads with low energy consumption and simple process were prepared, solving the problems of high energy consumption and complex operation in the existing technology, and achieving efficient and environmentally friendly ceramic microbead preparation.
Patent Information
- Application Number
- CN202310205118.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-06
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2043-03-06
AI Technical Summary
The existing porous ceramic microbead preparation methods have high energy consumption and complex operation, making it difficult to meet the requirements of low energy consumption and simplicity of operation at the same time.
Ceramic slurry is prepared by sol-gel method, and a porous structure is formed by adding microsphere foaming agent, combined with ultrasonic atomization and low-temperature heating molding, reducing the preparation temperature and energy consumption, and adding graphene dispersion to impart antibacterial ability.
It realizes low energy consumption and simple preparation of porous ceramic microbeads, has high compressive strength, high porosity and broad-spectrum antibacterial ability, expanding its application range.
Smart Images

Figure QLYQS_1 
Figure BDA0004110554610000011 
Figure BDA0004110554610000021
Abstract
Description
Technical Field
[0001] The invention belongs to the field of powder materials, and in particular relates to antibacterial porous ceramic microbeads and a preparation method thereof. Background Art
[0002] Porous ceramic microbeads are a new type of powder material developed in recent years. They are porous spherical powders with a particle size of 20-500 microns. They have the advantages of light weight, large volume, low thermal conductivity, high compressive strength, good dispersibility, fluidity and stability. They can play the role of heat insulation and sound insulation, reduce product weight, improve compression resistance and impact resistance, etc., and can also be used as functional fillers.
[0003] The main components of porous ceramic microspheres are silicon dioxide and aluminum oxide. They are generally obtained by grinding ceramic powders, pigments, fillers and solvents to form a slurry, then atomizing and sintering at a high temperature of more than 700°C. The energy consumption is very high. For example, the Chinese invention patent with patent number ZL201910103088.2 discloses a technical solution for a sintering method and device for hollow ceramic microspheres, which requires sintering under a high-temperature flame of 700-2000°C; the Chinese invention patent with publication number 201710152340.X discloses a technical solution for hollow ceramic microspheres with both thermal insulation and high thermal reflectivity, which is first calcined at 580-650°C for 2-4 hours, and then heated to 900-1000°C for calcination for 2-4 hours.
[0004] In summary, although most existing preparation methods can produce porous ceramic microspheres that meet different needs, it is difficult to simultaneously meet the requirements of low energy consumption and simple operation. Therefore, it is necessary to find a method for preparing porous ceramic microspheres with low energy consumption and simple operation. Summary of the invention
[0005] The purpose of the present invention is to provide an antibacterial porous ceramic microbead and a preparation method thereof in view of the technical problems in the above background. The present invention solves the following technical problems: how to reduce the preparation temperature and energy consumption of the porous ceramic microbeads, and endow the porous ceramic microbeads with broad-spectrum antibacterial properties, thereby expanding the application range of the porous ceramic microbeads.
[0006] The purpose of the present invention can be achieved by the following scheme:
[0007] The present invention is an antibacterial porous ceramic microbead, which is formed by curing a ceramic slurry, wherein the ceramic slurry comprises the following components in mass fractions:
[0008]
[0009]
[0010] As an embodiment of the present invention, the particle size of the silicon dioxide particles in the silica sol is 80-150nm, and the solid content is ≥40%, such as SD10050 of Dongguan Huihe Yongsheng Nanotechnology Co., Ltd. and LS100 of Shandong Better New Materials Co., Ltd. Silica sol is the main film-forming substance of the sol-gel reaction. If the particle size is small and the solid content is low, the compressive strength of the generated ceramic microbeads will be low. The methyltrimethoxysilane used in the present invention is an auxiliary film-forming substance for the sol-gel reaction. It is the silane with the fastest hydrolysis rate, which can shorten the reaction time and improve production efficiency. Aluminum sol cannot be used in the present invention. The viscosity of the slurry ground from aluminum sol is too large, and mist droplets cannot be sprayed out during ultrasonic atomization in the later stage, which is easy to clog the nozzle.
[0011] As an embodiment of the present invention, the mass percentage concentration of the NaOH solution is 1-1.5%: the pH value of the slurry is adjusted to above 9.5. NaOH is selected because it is common and cheap, has suitable alkalinity, and is easy to adjust the pH value; if a stronger base (such as KOH) is selected, it needs to be prepared into a solution with a lower concentration, and more water is introduced into the formula, which will lead to a decrease in solid content and low compressive strength of the ceramic microbeads; if a weaker base (such as Na2CO3) is selected, the pH adjustment effect is too weak and the pH value changes little.
[0012] As an embodiment of the present invention, the solid content of graphene in the graphene dispersion is 20-30%. The graphene dispersion can increase the toughness and strength of the porous ceramic microbeads and also give the system good broad-spectrum antibacterial properties. The graphene dispersion is WJ-WG01.
[0013] As an embodiment of the present invention, the filler includes one or more of calcined kaolin, heavy calcium, mica powder, talc, silica powder, whisker silicon, and alumina powder. The pigment includes titanium dioxide; the pigment in the present invention provides color, and ceramic microbeads are mostly white, so titanium dioxide is mostly used.
[0014] As an embodiment of the present invention, the weak acid includes one or more of formic acid and acetic acid. The mass percentage concentration of the formic acid solution is 20-30%, preferably 25%. The mass percentage concentration of the acetic acid solution is higher than 90%, or it is undiluted acetic acid. Due to its weak acidity, the amount of acetic acid added needs to be slightly increased. The weak acid is a sol-gel reaction catalyst. After the coating is prepared, the pH value is controlled between 4.2 and 4.8; if the amount of pure formic acid added is too small, a small amount of addition error can cause a large fluctuation in the pH value of the coating. Diluting the formic acid into a solution of about 25% can reduce the pH fluctuation caused by the addition error.
[0015] As an embodiment of the present invention, the microsphere foaming agent is a spherical plastic particle with a core-shell structure, the shell is a thermoplastic acrylic resin polymer, and the core is composed of alkane gas. After heating, the volume can expand rapidly to more than ten times or even dozens of times of itself, so as to achieve the foaming effect, so that a sponge-like porous structure is formed inside the ceramic microspheres, and the pore size is about 30-100μm. The porosity of the microspheres can be adjusted according to the amount of addition. If the amount is too much, the porosity is high. If it is too high, the compressive strength is reduced and it is easy to break during use; if the amount is too low, the porosity is low, and if it is too low, it cannot play its role. The microsphere foaming agent is preferably one of Aksu 951DU120 and Matsumoto Oil F-103K.
[0016] The present invention also provides a method for preparing the antibacterial porous ceramic microbeads, the method comprising the following steps:
[0017] S1. Preparation of ceramic slurry:
[0018] S1-1. Preparing a color paste: Weighing each component in proportion, mixing silica sol, NaOH solution, filler, pigment, and deionized water, grinding, filtering, adding graphene dispersion to the filtrate, and mixing evenly to obtain a color paste;
[0019] S1-2, methyltrimethoxysilane and part of isopropanol are mixed evenly, and then a weak acid is added and mixed evenly, and then poured into the obtained color paste and mixed evenly, and stirred for reaction to obtain a mixed slurry;
[0020] S1-3, the microsphere foaming agent is mixed evenly with the remaining isopropanol, and then added into the obtained mixed slurry, and mixed evenly to obtain a ceramic slurry.
[0021] S2. Preparation of porous ceramic microbeads:
[0022] The obtained ceramic slurry is ultrasonically atomized to form slurry droplets, which are then heated and formed to obtain antibacterial porous ceramic microbeads.
[0023] As an embodiment of the present invention, in step S1-1, the grinding fineness is less than 20 μm, and the grinding is carried out on a grinder so that the particle size of the solid particles is less than 20 μm; the filtration is performed using a 250-350 mesh filter cloth, preferably 300 mesh.
[0024] As an embodiment of the present invention, in step S1-2, part of the isopropanol refers to 40-60% of the total weight of isopropanol; the rotation speed during stirring is 100-180 rpm; the time is 4-5 hours, and the temperature is 10-35°C.
[0025] As an embodiment of the present invention, in step S1-3, the coating viscosity of the ceramic slurry is controlled between 12-18s, otherwise the nozzle is easily blocked during atomization, and the fineness of atomization is not enough to produce porous ceramic microbeads with small particle size. The ceramic slurry is obtained by sol-gel reaction. First, silane is hydrolyzed under the catalysis of organic acid to generate silanol, and then silanol and silica sol undergo condensation reaction to form a macromolecule with a Si-O-Si cross-linked structure, which is a porous structure with nanopores after curing.
[0026] As an embodiment of the present invention, in step S2, ultrasonic atomization is to add ultrasonic atomization equipment to atomize the slurry droplets, and spray them into the molding chamber, and heating molding is performed in the molding chamber. In the molding chamber, as the temperature rises, the microsphere foaming agent expands due to heat, and multiple pores are formed inside the slurry droplets, and the slurry droplets gradually lose water and dry and solidify to form porous ceramic microbeads; since the volume of the microsphere foaming agent can expand to dozens of times its own volume, it can form pores of hundreds of microns.
[0027] As an embodiment of the present invention, in step S2, the temperature of heating molding is 100-220°C, and a gradually increasing three-stage heating method is adopted. The temperature of the first stage is 100-130°C, and the heating time is 1-2 minutes; the temperature of the second stage is 140-180°C, and the heating time is 1-3 minutes; the temperature of the third stage is 190-220°C, and the heating time is 8-10 minutes. During the first temperature process in the molding chamber, the microsphere foaming agent begins to expand thermally, micropores begin to form inside the slurry droplets, and reach a state close to surface dry, that is, the inside is in a liquid state, the surface is not solidified but it is not sticky to the touch; during the second temperature process, the microsphere foaming agent reaches the maximum foaming state, multiple micropores are formed inside the slurry droplets, and the surface is solidified, and the inside is not completely solidified; during the third temperature process, the slurry droplets reach a completely solidified state.
[0028] In the present invention, porous ceramic microbeads with good quality and function need to form a large number of micropores with small and uniform pores, which are mainly adjusted by the amount of microsphere foaming agent added and the curing temperature. The more the amount of microsphere foaming agent added, the more micropores are formed, and too much will reduce the compressive strength; the pore size is mainly determined by the curing temperature of the first and second stages. After the first stage of curing, the microspheres begin to foam and the slurry viscosity begins to increase. When entering the second stage of curing, although the microsphere foaming agent can reach the maximum foaming ratio, the slurry viscosity further increases, forming a certain resistance to foaming, which is conducive to the formation of uniform small holes.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] (1) The present invention firstly prepares ceramic slurry by sol-gel method instead of ceramic slurry obtained by conventional mixing methods such as ceramic powder, clay, sand mud, etc., and forms a porous structure inside the ceramic microspheres by adding microsphere foaming agent, and then obtains porous ceramic microspheres by low temperature (100-220°C) heating and molding after atomization. Compared with porous ceramic microspheres prepared by conventional sintering method, the preparation temperature and energy consumption are greatly reduced, and the steps are simple.
[0031] (2) The porous ceramic microspheres obtained by the present invention have a Si-O-Si cross-linked structure as the skeleton, and are micropores of a nano-micron multi-level structure, wherein the sol-gel method forms nanostructured micropores, the expansion of the microsphere foaming agent can form microstructured micropores, and a small and uniform pore size structure is obtained by segmented heating. The porous ceramic microspheres have the characteristics of high compressive strength, high porosity, and a wide range of applications;
[0032] (3) Since graphene dispersion is added to the ceramic slurry, the porous ceramic microspheres have a broad-spectrum antibacterial effect, and have excellent bactericidal and antibacterial effects on Staphylococcus aureus, Escherichia coli, Candida albicans, Pseudomonas aeruginosa, fungi, etc. DETAILED DESCRIPTION
[0033] The present invention is described in detail below in conjunction with specific embodiments. The following examples are implemented under the premise of the technical solution of the present invention, and provide detailed implementation methods and specific operation processes, which will help those skilled in the art to further understand the present invention. It should be pointed out that the protection scope of the present invention is not limited to the following embodiments, and several adjustments and improvements made under the premise of the concept of the present invention all belong to the protection scope of the present invention.
[0034] Example 1
[0035] This embodiment provides an antibacterial porous ceramic microbead, which is formed by curing a ceramic slurry. The specific preparation method is as follows:
[0036] (1) Weighing raw materials according to the mass fraction in Table 1, mixing silica sol, NaOH solution, filler, pigment, and deionized water, grinding on a grinder to a fineness of less than 20 μm, filtering with a 300-mesh filter cloth, adding graphene dispersion, and mixing evenly to obtain a color paste;
[0037] (2) Methyltrimethoxysilane and 40% isopropanol were mixed evenly, and then formic acid solution was added and mixed evenly, and then poured into the obtained color paste and mixed evenly, and stirred for reaction at 25° C. and 120 rpm for 4.5 hours to obtain a mixed slurry;
[0038] (3) The microsphere foaming agent is mixed evenly with the remaining 60% of isopropanol, and then added to the obtained mixed slurry, and mixed evenly to obtain a ceramic slurry. The coating-4 cup viscosity of the ceramic slurry is 16.8s;
[0039] (4) The obtained ceramic slurry is added to an ultrasonic atomizing device to be atomized to form slurry droplets, which are then sprayed into a molding chamber. A three-stage heating method with gradually increasing temperatures is adopted in the molding chamber: the first stage temperature is 120°C, and the heating time is 2 minutes; the second stage temperature is 160°C, and the heating time is 2.5 minutes; the third stage temperature is 200°C, and the heating time is 9 minutes, thereby obtaining antibacterial porous ceramic microbeads.
[0040] Table 1
[0041]
[0042]
[0043] Among them, the silica sol particle size in Table 1 is 100-120nm (SD10050 of Dongguan Huihe Yongsheng Nano Technology Co., Ltd.), the solid content is 50%, the mass percentage concentration of NaOH solution is 1%, the graphene dispersion liquid is WJ-WG01 (Hefei Microcrystalline Material Technology Co., Ltd.), the microsphere foaming agent is Aksu 951DU120, and the mass percentage concentration of formic acid solution is 25%.
[0044] Example 2
[0045] The present embodiment provides an antibacterial porous ceramic microbead, which is formed by curing a ceramic slurry. The components are shown in Table 1. The preparation method is basically the same as that in Example 1, wherein the heating method is as follows: the temperature of the first section is 100°C, and the heating time is 2 minutes; the temperature of the second section is 180°C, and the heating time is 1 minute; the temperature of the third section is 220°C, and the heating time is 8 minutes, thereby obtaining antibacterial porous ceramic microbeads.
[0046] Example 3
[0047] The present embodiment provides an antibacterial porous ceramic microbead, which is formed by curing a ceramic slurry. The components are shown in Table 1. The preparation method is basically the same as that in Example 1, wherein the heating method is as follows: the temperature of the first section is 130°C, and the heating time is 1 minute; the temperature of the second section is 140°C, and the heating time is 3 minutes; the temperature of the third section is 190°C, and the heating time is 10 minutes, thereby obtaining antibacterial porous ceramic microbeads.
[0048] Example 4
[0049] This embodiment provides an antibacterial porous ceramic microbead, which is formed by curing a ceramic slurry. The components are shown in Table 1, and the preparation method is the same as that of Example 1.
[0050] Comparative Example 1
[0051] This comparative example provides an antibacterial porous ceramic microbead, which is formed by curing a ceramic slurry. The preparation method is basically the same as that of Example 1, and the only difference is that the silica sol in the component is different and the particle size is 20-30 nm.
[0052] Comparative Example 2
[0053] This comparative example provides an antibacterial porous ceramic microbead, which is formed by curing a ceramic slurry. The preparation method is basically the same as that of Example 1, and the only difference is that the silica sol in the component is replaced by alumina sol.
[0054] Comparative Example 3
[0055] This comparative example provides an antibacterial porous ceramic microbead, which is formed by curing a ceramic slurry. The preparation method is basically the same as that of Example 1, except that no graphene dispersion is added to the components. The prepared porous ceramic microbeads were tested for antibacterial effects, and the results showed that bacteria reproduced normally, and the antibacterial effect was not achieved.
[0056] Comparative Example 4
[0057] This comparative example provides an antibacterial porous ceramic microbead, which is formed by curing a ceramic slurry. The preparation method is basically the same as that of Example 1, except that the molding chamber adopts a one-stage heating, the temperature is 190-220°C, and the time is 10-15min. Foaming is a gradual process. Direct heating will cause a sudden increase in viscosity, and there is no time for complete foaming, so the foaming ratio is low and the true porosity formed is low. The foaming ratio of Comparative Example 4 is relatively low, so the foaming is insufficient and the pore distribution is uneven.
[0058] The ceramic microbeads prepared in the examples and comparative examples were tested for their main properties, and the results are shown in Table 2:
[0059] Table 2
[0060]
[0061] The present invention also carried out antibacterial testing, the standard or method was GB / T 21866-2008, and the results are shown in Table 3.
[0062] Table 3
[0063]
[0064] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.
Claims
1. A method for preparing antibacterial porous ceramic microbeads, characterized in that: The preparation method comprises the following steps: S1. Preparation of ceramic slurry: S1-1. Preparing a color paste: Weighing each component in proportion, mixing silica sol, NaOH solution, filler, pigment, and deionized water, grinding, filtering, adding graphene dispersion to the filtrate, and mixing evenly to obtain a color paste; S1-2, methyltrimethoxysilane and part of isopropanol are mixed evenly, and then a weak acid is added and mixed evenly, and then poured into the obtained color paste and mixed evenly, and stirred for reaction to obtain a mixed slurry; S1-3, mixing the microsphere foaming agent and the remaining isopropanol evenly, and then adding them to the obtained mixed slurry, mixing evenly, to obtain a ceramic slurry; S2. Preparation of porous ceramic microbeads: The obtained ceramic slurry is ultrasonically atomized to form slurry droplets, and then heated to form antibacterial porous ceramic microbeads; In step S1, the ceramic slurry includes the following components in mass fractions: In step S2, the heating molding temperature is 100-220°C, and a gradually increasing segmented heating method is adopted; the segmented heating method is specifically as follows: the temperature of the first section is 100-130°C, and the heating time is 1-2 minutes; the temperature of the second section is 140-180°C, and the heating time is 1-3 minutes; the temperature of the third section is 190-220°C, and the heating time is 8-10 minutes.
2. The method for preparing antibacterial porous ceramic microbeads according to claim 1, characterized in that The particle size of the silicon dioxide particles in the silica sol is 80-150 nm, and the solid content is ≥40%.
3. The method for preparing antibacterial porous ceramic microbeads according to claim 1, characterized in that: The filler includes one or more of calcined kaolin, heavy calcium, mica powder, talcum powder, silica powder, whisker silicon, and alumina powder; and the pigment includes titanium dioxide.
4. The method for preparing antibacterial porous ceramic microbeads according to claim 1, characterized in that: The weak acid includes one or more of formic acid and acetic acid.
5. The method for preparing antibacterial porous ceramic microbeads according to claim 1, characterized in that: The microsphere foaming agent includes one of Aksu 951DU120 and Matsumoto Grease F-103K.
6. The method for preparing antibacterial porous ceramic microbeads according to claim 1, characterized in that: In step S1-1, the grinding fineness is less than 20 μm; and the filtration is performed using a 250-350 mesh filter cloth.
7. The method for preparing antibacterial porous ceramic microbeads according to claim 1, characterized in that: In step S1-2, during the stirring reaction, the rotation speed is 100-180 rpm, the time is 4-5 hours, and the temperature is 10-35°C.
Citation Information
Patent Citations
Hollow ceramic micro-bead with heat insulation properties and high heat reflection rate
CN106905752A
A sintering method and apparatus for hollow ceramic microspheres
CN111517757B
Antibacterial and antiviral inorganic ceramic interior wall coating and preparation method thereof
CN113122086A
High-temperature-resistant long-acting non-stick ceramic coating and preparation method thereof
CN115322598A
Heat Shield Component and Manufacturing Method Thereof
US20200369576A1